Adult ileocolic intususception: a case report - Kumar Yadav, Akhilesh; Goel, Tushar; Thawait, Anand; Dwivedi, Sankalp (International Surgery Journal, 2017)
Intussusception is defined as the pathology in which a segment of intestine telescopes into the adjoining intestinal lumen. Ileocolic accounts for 75% of all cases of intussusception. The average age of affected adults is between 50 and 60 years old and it occurs more often in women. The higher percentage of intussusception in adults (65%) occurs due to malignant or benign neoplasms. Appendix is part of intussusception of commonest ileocolic type but appendix as lead point for intussusception is rare. Patient details were collected by patient’s IPD file. Complete detailed history, patient vitals, hemogram, ABO, with X-ray Abd erect, USG abdomen and CECT abdomen was done. Post-OP patient was followed by USG review. 60-year-old female diagnosed and operated as for ileocolic intussusception with appendix as lead point. Ileo transverse anastomosis was performed with hemicolectomy involving the terminal ileum along with caecum and ascending colon. Post op patient did well passed stools on 5th day. Intussusception is a pathology in which a segment of intestine telescopes into the adjoining intestinal lumen causing intestinal obstruction. Intussusception are two types antegrade and retrograde. CT scan and colonoscopy, which provide an accurate diagnosis, allowed the best surgical choice in the hands of an experienced surgeon.